2001
DOI: 10.1101/lm.41701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age and Level of Cognitive Function on Spontaneous and Exploratory Behaviors in the Beagle Dog

Abstract: Cognitively characterized young and aged beagle dogs were administered six different spontaneous behavior tests, which provided measures of locomotion, exploration, and social interaction. Consistent with our previous findings, we obtained no overall effect of age on locomotion. We did find, however, that for the aged dogs locomotion correlated with level of cognitive function, being lowest in age-unimpaired dogs and highest in impaired dogs. Exploratory behavior, as measured by response to novelty, varied wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
3
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 41 publications
2
67
3
2
Order By: Relevance
“…In particular, dogs impaired on neuropsychological tests are more likely to demonstrate increased activity levels compared to age-matched cognitively normal dogs (Siwak et al 2001(Siwak et al , 2003. Impaired dogs, when compared to young dogs or cognitively intact older dogs, spend less time close to or in contact with humans (Siwak et al 2001). These results suggest that noncognitive behavioral changes also occur with severe cognitive impairment, which may partially model the noncognitive behavioral changes seen in human dementia.…”
Section: Age-associated Cognitive Decline In Dogsmentioning
confidence: 89%
See 1 more Smart Citation
“…In particular, dogs impaired on neuropsychological tests are more likely to demonstrate increased activity levels compared to age-matched cognitively normal dogs (Siwak et al 2001(Siwak et al , 2003. Impaired dogs, when compared to young dogs or cognitively intact older dogs, spend less time close to or in contact with humans (Siwak et al 2001). These results suggest that noncognitive behavioral changes also occur with severe cognitive impairment, which may partially model the noncognitive behavioral changes seen in human dementia.…”
Section: Age-associated Cognitive Decline In Dogsmentioning
confidence: 89%
“…It is unclear to what extent CDS is related to neuropsychological deficits; however, evidence from laboratory-based noncognitive behavioral testing suggests a link. In particular, dogs impaired on neuropsychological tests are more likely to demonstrate increased activity levels compared to age-matched cognitively normal dogs (Siwak et al 2001(Siwak et al , 2003. Impaired dogs, when compared to young dogs or cognitively intact older dogs, spend less time close to or in contact with humans (Siwak et al 2001).…”
Section: Age-associated Cognitive Decline In Dogsmentioning
confidence: 99%
“…Possibly a more important reason for the diversity in reversal learning data is individual differences associated with aging. Our studies of cognitive aging in beagle dogs have indicated that individual variability in cognitive performance increases with age such that at least three distinct populations of aged dogs can be identified: those that are severely cognitively impaired, those that show mild impairments, and those that perform at levels similar to those of young dogs (Milgram et al 1994;Head et al 1995;Cummings et al 1996a,b;Adams et al 2000a;Head et al 2001;Siwak et al 2002). To account for this age-associated increase in cognitive variability, the present study separated aged dogs into two distinct groups based on chronological age.…”
Section: Tapp Et Almentioning
confidence: 98%
“…Open-field arena All non-cognitive tests (see Siwak et al 2001) occurred in a room measuring 274.32×252.73 cm. To facilitate tracking a subject during videotape analysis, strips of electrical tape were applied to the floor in a grid pattern.…”
Section: Open Field Activity and Exploratory Behaviormentioning
confidence: 99%